Evaluation of the Structural Performance Behavior of Hotel Building Y in Palu City, Central Sulawesi, Indonesia using the Pushover Analysis Method after the 2018 Earthquake Event (SNI Approach for Earthquake-Resistant Buildings) - Ayuddin, .; Hsiao, Po-Chien (Engineering, Technology & Applied Science Research, 2025)
The purpose of this research is to assess the structural performance level resulting from the assessment through ETABS software based on FEMA 440 regulations on the planning of the Y Hotel building in Palu City, Central Sulawesi, Indonesia after being analyzed by the pushover analysis method after the 2018 earthquake. The study subject is the upper structure of the Hotel Y building, namely the columns, beams, plates, and roofs. Data analysis techniques were carried out according to the rules of load simplification. Three-dimensional modeling of the building was conducted using the ETABS softwar before the analysis and pushover stages for performance evaluation. In accordance with the design of the Hotel Y building, the total height is 56 m with 15 stories, using reinforced concrete structures to provide optimal stability and strength. The basic Y-shape was chosen to maximize space distribution and increase visual appeal. The material qualities used were Fc’ 35 Mpa and 30 Mpa, Fy’ = 400 Mpa, Ec = 4700√(fc’), BJTP 24, and BJTD 40. The analysis of loading calculations was conducted in accordance with SNI 1727: 2020 and SNI 1726: 2019 standards, including dead load, live load, fixed additional load, rain load, roof live load, wind load, and earthquake load. The results of this study obtained an effective base shear force greater than the plan shear force, namely V